The plasma focus-trending into the future - Lee, S.; Saw, S. H. (Wiley Online Library, 2012)
The plasma focus is a promising small-scale alternative to the huge Tokamak project in the development of nuclear fusion energy. Its strength lies in the characteristic that the plasma condition is the same whether the plasma focus is a small sub-kilojoule machine or a large one with thousands of kilojoules of stored energy and the related constancy of the dynamic resistance. Yet, this strength turns out to result in a weakness. The observed neutron ‘saturation’ is more correctly stated as a ‘scaling deterioration’ effect. This critical weakness is due to the same constancy of the plasma condition intimately related to a constancy of the dynamic resistance. The understanding of this situation points to a new class of plasma focus devices to overcome the ‘saturation’ of the electric current. Plasma focus technology has to move to ultra high voltage technology and take advantage of circuit manipulation techniques in order to move into a new era of high performance. This paper examines fundamental scaling properties of the plasma focus including speeds, temperatures, dimensions and times. It links up these basic scaling characteristics with the crucial ideas of the inherent yield scaling deterioration, thus providing a clear understanding of its overall performance characteristics, paving the way for future exploitation. Copyright © 2011 John Wiley & Sons, Ltd.